Tree Species Richness, Phytomass Carbon Stock and Soil Organic Carbon in Tropical Deciduous Barandabhar Forest, Chitwan, Nepal - Gautam, Vishnu Prasad; Sharma, Bhuvan Keshar; Baniya, Chitra Bahadur; Yadav, Ram Kailash Prasad (Banko Janakari, 2026)
Assessing carbon stocks in forest ecosystems is essential for the development of effective management strategies. This study was carried out with aim to assess the tree species richness, phytomass carbon stock, and soil organic carbon (SOC) in Barandabhar forest in Chitwan, Bagmati Province, Nepal under four management regimes within forest such as: Buffer Zone Forest (BZ), Buffer Zone Community Forest (BZCF), Community Forest (CF), and Protected Forest (PF) using concentric circular plots of 20 m radius (each of 0.12 ha). Altogether 256 sample plots were employed. Among them, 119 plots were in BZ, 48 plots in BZCF, 56 plots in CF, and 33 plots in PF. All tree species in each plot were recorded and their height and diameter at breast height (DBH ≥ 5cm) were measured to calculate phytomass carbon stock. Soil parameters such as pH, Bulk density, and SOC for soil samples collected from 0–10 cm depth in each plot were also analysed. In total, 30 tree species were recorded in the study, with Shorea robusta contributing the highest phytomass carbon stock. The mean phytomass carbon stock across the study area was 201±5 t/ha, while the mean SOC in the soil was 10.2±0.2 t/ha. Across the regimes, the highest phytomass carbon stock was recorded in the BZCF i.e., 239 ± 14 t/ha, followed by PF (207 ± 12 t/ha), BZ (202 ± 6 t/ha), and CF (162 ± 8 t/ha), respectively. The better predictors of phytomass carbon were soil pH and bulk density including tree basal area. These findings emphasize that forest management practices could have a significant impact on the carbon storage potential of forests.